Motivation in rural math education within general and special education settings - Jackson, Haidee A.; Starrett, Angela; Bottoms, Bryndle (Frontiers in Education, 2025)
IntroductionThis study examines how motivational processes in STEM education differ for rural students with and without Individualized Education Programs (IEPs) using Situated Expectancy-Value Theory (SEVT). The study advances theoretical understanding of STEM motivation in underrepresented populations and provides practical recommendations for creating inclusive rural STEM programs that leverage community strengths while meeting diverse learner needs.MethodsAnalyzing data from 1,957 rural high school students (444 with IEPs) in the HSLS:09 dataset, we established measurement invariance for four SEVT constructs-intrinsic value, utility value, expectancies for success, and teacher perceptions-confirming their equivalent measurement across groups.ResultsResults revealed students with IEPs reported slightly higher expectancies for success (β = 0.145, p < 0.05) but showed no differences in other motivational factors compared to peers without IEPs. Structural analyses demonstrated intrinsic value significantly predicted math effort (β = 0.219) and STEM aspirations (OR = 1.45) only for students without IEPs, while no motivational constructs predicted outcomes for IEP students despite their stronger baseline expectancies. Indirect effects with teacher perceptions were significant for both groups, suggesting educators play a crucial role in shaping motivation.DiscussionThese findings challenge assumptions about motivation deficits in special education populations while highlighting the need for differentiated interventions that address the unique barriers preventing rural students with IEPs from translating motivation into STEM engagement.